The complete chloroplast genome of Dendrobium moschatum (Buch.-Ham.) Sw. 1805 (Orchidaceae). Issue 12 (2nd December 2022) - Yang, Yan-Bing; Yan, Feng-Xia; Wang, Lian-Hui; Tian, Fan; Zhou, Feng-Jiao
Abstract: The morphological characteristic of Dendrobium moschatum (Buch.-Ham.) Sw. 1805 is very distinctive among Dendrobium Sw. 1799, and it has high medicinal and ornamental values. Here, we reported the first complete chloroplast genome of D. moschatum . The complete genome of D. moschatum was 159, 701 bp in length with 130 genes, including 38 tRNA, 8 rRNA, and 84 protein-coding genes. Phylogenetic analysis showed that D. moschatum was strongly allied with D. denneanum Kerr. 1933.